2017
DOI: 10.1039/c6ra25704f
|View full text |Cite
|
Sign up to set email alerts
|

Proposition and computational analysis of a kesterite/kesterite tandem solar cell with enhanced efficiency

Abstract: An all-kesterite tandem junction solar cell has been proposed and an efficiency ≥20% has been estimated from computational analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 59 publications
3
27
0
Order By: Relevance
“…Aluminum doped ZnO (AZO) is used to reduce the series resistance of the cell. 17 The thickness of AZO, ZnO, CdS(n), CZTS(p+) are 400, 50, 100, 200 nm, respectively. We varied the thickness of ACZTS(p) in this study to maximize the efficiency of our structure.…”
Section: Device Structure and Simulation Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…Aluminum doped ZnO (AZO) is used to reduce the series resistance of the cell. 17 The thickness of AZO, ZnO, CdS(n), CZTS(p+) are 400, 50, 100, 200 nm, respectively. We varied the thickness of ACZTS(p) in this study to maximize the efficiency of our structure.…”
Section: Device Structure and Simulation Methodologymentioning
confidence: 99%
“…2 and Table 1 show the J-V characteristic and comparison between our simulation and experimental results, 8,15 respectively. The optical and basic electrical parameters as well as recombination parameters were taken from literature (optical; 20,21,[28][29][30] electrical 8,17,[19][20][21][22][23][24][31][32][33][34][35][36][37][38] (listed in Table 2)). In this respect, we have used minority carrier life time of CZTS 0.47 ns and 0.72 ns for matching with the experimental results of Shin et al 8 and Sun et al 15 respectively.…”
Section: A Model Vericationmentioning
confidence: 99%
“…The computational analysis by Alam et al . shows that 21.74% efficiency could be achieved by their proposed eco‐friendly kesterite CZTS/CZTSe tendam solar devices design with optimized band gaps . However, many other quaternary analogues Cu 2 M I M II X 4 are still at the initial stages of development and their PV efficiencies are yet to be evaluated ,,,,,,.…”
Section: Applications Of Quaternary Chalcogenidesmentioning
confidence: 99%
“…As a result, current density falls significantly with the higher thickness of CZTS (Figure 2(a)) because of the reduced optical power absorption in the bottom cell. Thus, higher thickness of [19] 7 [18] 8.5 [17] 7 [16] Band gap (eV) 1.9 [14] 1.45 [18] 0.97 [17] 0.9 [16] Electron affinity (eV) 3.6 [19] 4.1 [24] 4.05 [17,25] 4.05 [13] Electron effective mass (m e /m o ) 0.37 [14,15] 0.18 [13,16] 0.08 [17] 0.07 [13,16] Hole effective mass (m p /m o ) 1.68 [14] 2 [13,16] 0.3 [17] 0.2 [13,16] Electron mobility (cm 2 V À1 s À1 ) 3 0 [26] 40 [21,24] 75 [23] 145 [13,21] Hole mobility (cm 2 V À1 s À1 ) 1 0 [27] 25 [21] 1 [17,23] 35 [13,21] Acceptor concentration (cm…”
mentioning
confidence: 99%
“…In a previous report, we have recently proposed a dual junction CZTS (top cell)/CZTSe (bottom cell) tandem solar cell with 19.87% efficiency. [13] Further improvements in this direction need suitable bandgap materials for efficient absorption and carrier generation. Recently, Shin et al [14] demonstrated a solar cell of 5.2% PCE with Cu 2 BaSnS 4Àx Se x (CBTSSe) whose bandgap can be in the range of %1.6-2.0 eV [15] making it suitable for the top cell of a triple junction chalcogenide solar cell.…”
mentioning
confidence: 99%